Analisis Penerapan Manajemen Rantai Pasok Ramah Lingkungan pada PT. X - Widyacantika, Sarah Ayu; Azis, Anton Mulyono (STIE Ekuitas, 2020)
PT X is the only vaccine manufacturer in Indonesia and the largest in Southeast Asia to implement green industry processes in every business process. However, in practice, some of the challenges that arise today, the green industry first in the management of waste from the production of vaccines. This study discusses the supply chain process carried out by the concept of environmental supply chain management, knowing the constraints in the supply chain process and its compliance with ISO 14001: 2004 and PROPER. The research method used is descriptive using qualitative data conducted by interview, observation, and literature study. Data processing is done using tools that consist of charts and check sheets. Based on the results of research contained in the green manufacturing process that involves a damaged engine control system, the green distribution process is caused by the absence of the application of green transportation, and reverse logistics which leads to savings of experts in the waste treatment process. From these problems, it can be concluded that in the process of environmentally friendly supply chain management in PT X caused by human and machine factors. Keywords: ISO 14001: 2004, PROPER, Green Transport, Reverse Logistics.